Comfort woman a Filipina's story of prostitution and slavery under the Japanese military - Henson, Maria Rosa L. 1927- (Rowman & Littlefield, 2017)
"In April 1943, fifteen-year-old Maria Rosa Henson was taken by Japanese soldiers occupying the Philippines and forced into prostitution as a 'comfort woman.' In this simply told yet powerfully moving autobiography, Rosa recalls her childhood as the illegitimate daughter of a wealthy landowner, her work for Huk guerrillas, her wartime ordeal, and her marriage to a rebel leader who left her to raise their children alone. Her triumph against all odds is embodied by her decision to go public with the secret she had held close for fifty years. Now in a second edition with a new introduction and foreword that bring the ongoing controversy over the comfort women to the present, this powerful memoir will be essential reading for all those concerned with violence against women"--Back cover.